Wybiórczość poznawcza umysłu w sferze pamięci - Hankała, Andrzej (Filozofia Nauki, 1993)
The central - and philosophically important - question connected with selectivity is the question of the nature of this phenomenon as a specific feature of human cognitive system. It is revealed in acts of two types. Acts of the first type are selective extraction of concrete as well as symbolic informations derived from the external world, and contained in sensoric representations. Acts of the second type are selective actualization of informations preserved in an individual permanent memory. The hypothesis of existing general mental disposition common to acts of both the types is very attractive. The author analyzes some psychological (empirical) and philosophical aspects of these problems.